2007
DOI: 10.1159/000098956
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Morphometric Analysis of the Adrenal Cortex of Androgenized Female Rats

Abstract: Aim: We evaluated the thickness of the adrenal cortex zones of female rats androgenized to mimic polycystic ovary syndrome. Methods: Forty-four female virgin Wistar-Hannover rats were divided into two groups: controls (n = 17) and animals which received testosterone propionate on the 2nd day of life (n = 27). At 90 days of life, after confirmation of persistent estrus, the animals were sacrificed, and the adrenal cortex zones were evaluated. Student’s t test and Levene’s test were used in the statistical analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 39 publications
0
8
0
2
Order By: Relevance
“…39,41,42 These animals in adulthood present anovulation, higher LH secretion, polycystic ovaries and aggressive behavior when in contact with males, thus there is a resemblance to the human condition of polycystic ovary syndrome. 18,40 Furthermore, rats in persistent estrus may have hypertension, as shown in a study conducted by Gontijo et al 8 Those authors showed that rats in persistent estrus had a significant increase in arterial pressure, in comparison to rats in the control group. 8 trEatmEnt Regarding treatment, it is recommended to start with aggressive diet/lifestyle modifications which may lead to weight loss, improve anovulation and indirectly cause a reduction in systolic arterial pressure.…”
Section: Pcos and Hypertensionmentioning
confidence: 95%
See 1 more Smart Citation
“…39,41,42 These animals in adulthood present anovulation, higher LH secretion, polycystic ovaries and aggressive behavior when in contact with males, thus there is a resemblance to the human condition of polycystic ovary syndrome. 18,40 Furthermore, rats in persistent estrus may have hypertension, as shown in a study conducted by Gontijo et al 8 Those authors showed that rats in persistent estrus had a significant increase in arterial pressure, in comparison to rats in the control group. 8 trEatmEnt Regarding treatment, it is recommended to start with aggressive diet/lifestyle modifications which may lead to weight loss, improve anovulation and indirectly cause a reduction in systolic arterial pressure.…”
Section: Pcos and Hypertensionmentioning
confidence: 95%
“…17 Another site for androgen production is the adrenal cortex, due to abnormalities in cortical stereoidogenesis promoted by stimulation of adrenocorticotropic hormone. 18 And these excess androgen levels, mainly testosterone, androstenedione and dehydroepiandrosterone sulfate, cause premature atresia of ovarian follicles, forming multiple cysts and anovulation with persistent estrogen levels resulting from aromatization of androgens to estrogens without opposition of progesterone and associated with an increased risk of endometrial carcinoma. 19,20 clInIcal manIfEStatIonS and dIagnoSIS…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%
“…These epithelial cells are grouped into three different adrenocortical zones arranged as zona glomerulosa (ZG), zona fasciculate (ZF), and zona reticularis (ZR). The cells of ZG secrete significant amounts of the mineralcorticoids aldosterone, and ZF cells secrete the glucocorticoids cortisol and corticosterone, in addition to small amounts of adrenal androgens and estrogens, while ZR cells secrete the adrenal androgens androstenedione, dehydroepiandrosterone (DHEA) and small amounts of estrogens and some glucocorticoids (da Silva et al, 2007;Kutovaja and Bhatia, 2014).…”
Section: The Nd Supraphysiological Dose Groupmentioning
confidence: 99%
“…An external cortex covers a central medulla [1] . The cortex has three morphological zones differing in function: the zona glomerulosa, zona fasciculata, and zona reticularis [2] . These three zones play different roles in steroid hormone synthesis.…”
Section: Introductionmentioning
confidence: 99%